Pemetaan Erodibilitas Tanah Dan Korelasinya Terhadap Karakteristik Tanah Di Das Serang, Kulonprogo - Efrinda Ari Ayuningtyas; Ainul Fahmi Nur Ilma; Rindhang Bima Yudha (Penelitian dan Pengabdian Kepada Masyarakat Sekolah Vokasi Universitas Gadjah Mada, 2018)
Soil erosion was happened caused by many factors, such as rainfall intensity, soil erodbility, steepness and length of slope, land cover, and conservation practices. In other case, the soil properties also influence the vulnerability of soil to be detached. This soil properties characteristics is classified as soil erodibility. Erodibility factor (K) from the Universal Soil Loss Equation (USLE) in this study was the result of soil erodibility estimation or soil capability to be dispersed by rain. K factor was affected by soil organic, soil permeability, soil structures, and soil textures. This study was contributed in Serang Watershed because of the main fuction of this watershed to supply water resources especially in Sermo Reservoir in Ngrancah Subwatershed. This reservoir was used to distribute water and irrigation to all Kulonprogo District and especially to keep the sustainability of sedimentation of soastal area di Glagah Beach. All of soil properties was collected in each landform of Serang Watershed and was analyzed by laboratory measurement. By using K factor formula, the K value can be estimated. Geographic Information System (GIS) tools were used to map and represent the spatial information of soil erodibility of Serang Watershed. The result of this study showed that the high value of K factor was distributed in the area which has genesis of structural, denudated structural, and sedimented denudational. Furthermore, this study can be strived to analyze soil erosion hazard which was influenced by soil erodibility.